The perception of usefulness and utilization of learning management system among the teachers of Asia Pacific schools / Fariha Diyana Awang Ali - Awang Ali, Fariha Diyana (2014)
The purpose o f this study was to identify the teachers’ perception o f usefulness and utilization o f LMS in Asia Pacific Schools. The two schools from Asia Pacific Schools namely, Asia Pacific International School and Asia Pacific Smart School were selected for this study. Data were collected using questionnaire. The questionnaire was distributed to a total o f 120 randomly selected teacher respondents and 101 questionnaires were returned, appropriately completed and able to be used for analysis. Data were analyzed using descriptive and correlation statistics. The findings revealed that the seven dimensions o f teachers' perceptions were at moderate level. Among these variables, pedagogical dimension was identified at the low level. Teachers" perception o f usefulness was high on the instructional design, interactive design and visual features design o f the LMS. In addition, the findings indicated that there was moderate level o f utilization o f LMS among the teachers in Asia Pacific Schools. On the other hand, the findings indicated that there was a strong relationship between the seven dimensions o f the teachers’ perception o f usefulness and the utilization of LMS. The findings showed that the teachers’ perception o f usefulness of Learning Management System was highly affected by the teachers’ perception on the interactive design and instructional design o f the Learning Management System. It can be concluded from the lack utilization o f LMS among the teachers was mainly because of the teachers' perception on the pedagogy and the easy of use of LMS.